The value of punishment of free riders: A case study on the receiving fee system of the Japanese public broadcasting organization - Hisanobu Kakizawa (International Telecommunications Society (ITS), 2017)
Social preferences for the punishment of free riders are critical for generating cooperative behavior in human society. Focusing on the receiving fees of Japans public broadcaster, this study analyses how punishment of free riders, that is, the strengthening of legal responses against them, affects the willingness to pay (WTP) of general viewers. Preferences regarding punishments were found to have significant positive effects on WTP. Furthermore, differences of perception about the institutional framework around receiving fees and differences in type concerning cooperative behavior were found to influence these effects clearly.
Keywords: D63; H41; K42; 330; public goods; social preference; free riding; punishment; WTP